One‐pot Unsymmetrical Ketone Synthesis Employing a Pyrrole‐Bearing Formal Carbonyl Dication Linchpin Reagent. Issue 34 (3rd July 2015) - Heller, Stephen T.; Newton, James N.; Fu, Tingting; Sarpong, Richmond
Abstract: A one‐pot procedure for the synthesis of unsymmetrical ketones utilizing a pyrrole‐bearing carbonyl linchpin reagent (carbonyl linchpin N, O ‐dimethylhydroxylamine pyrrole; CLAmP) is reported. In contrast to other carbonyl dielectrophile equivalents, CLAmP enables the synthesis of ketones from a variety of organolithium and Grignard reagents. The electrophilic nature of CLAmP enables the addition of less reactive as well as thermally unstable nucleophiles. CLAmP was designed to form kinetically stable tetrahedral intermediates upon the addition of organometallic nucleophiles. Evidence for the existence of persistent tetrahedral intermediates was obtained through in situ IR studies. Abstract : Pot economy : Unsymmetrical ketones are readily and selectively prepared in one pot by the sequential addition of organometallic nucleophiles to N ‐methoxy‐ N ‐methyl‐1 H ‐pyrrole‐1‐carboxamide (CLAmP), a rationally designed carbonyl dication synthetic equivalent which forms tetrahedral intermediates that are persistent at the temperature of nucleophile addition but are kinetically labile at ambient temperature.